التوافق الدراسي وعلاقته بالدافعية للتعلم لدى تلاميذ السنة أولى ثانوي )دراسة مٌدانٌة بمقاطعة الدبٌلة بالوادي- الجزائر( - الهلي, مصباح; حمامة, عمار; مخلوفي, عبد الغني (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة الحالية إلى الكشف عن العلاقة إن وجدت بين التوافق الدراسي والدافعية للتعلم لدى تلاميذ السنة أولى ثانوي بمدينة الوادي- الجزائر، وباستخدام المنهج الوصفي الارتباطي، تمَ إجراء الدراسة على عينة قوامها 122 تلميذا وتلميذة من تلاميذ السنة أولى ثانوي خلال السنة الدراسية 2018/2019، وقد أختيروا بطريقة عشوائية بسيطة، وطبق عليهم إستبياني التوافق الدراسي لـلشناوي عبد المنعم الشناوي، والدافعية للتعلم لـيوسف قطامي، ، فكانت النتائج كالآتي: - توجد علاقة ذات دلالة إحصائية بين التوافق الدراسي والدافعية للتعلم لدى تلاميذ السنة أولى ثانوي بالوادي. - لا توجد فروق ذات دلالة إحصائية بين الجنسين في التوافق الدراسي لدى تلاميذ السنة أولى ثانوي بالوادي. - توجد فروق ذات دلالة إحصائية بين الجنسين في الدافعية للتعلم لدى تلاميذ السنة أولى ثانوي بالوادي لصالح الذكور. - لا توجد فروق ذات دلالة إحصائية بين التخصصين(أدبي/علمي) في التوافق الدراسي لدى تلاميذ السنة أولى ثانوي بالوادي. - لا توجد فروق ذات دلالة إحصائية بين التخصصين(أدبي/علمي) في الدافعية للتعلم لدى تلاميذ السنة أولى ثانوي بالوادي. الكلمات المفتاحية: التوافق؛ التوافق الدراسي؛ الدافعية؛ الدافعية للتعلم. Abstract: The current study aims to reveal the relationship, if any, between academic compatibility and motivation to learn among students of the first year of secondary school in the city of El-Oued – Algeria, Using the descriptive correlative approach, the study was conducted on a sample of 122 male and female students of the first year of secondary school during the academic year 2018/2019, and they were chosen in a simple random way, and the study compatibility questionnaire was applied to them by Abdul-Moneim Al-Shennawi, and the motivation to learn by Youssef Qatami, The results were as follows: - There is a statistically significant relationship between academic compatibility and motivation to learn among first-year secondary school students in the valley. - There are no statistically significant differences between the sexes in the academic adjustment of first-year secondary school students in the valley. - There are statistically significant differences between the sexes in the motivation to learn among first-year secondary school students in the valley in favor of males. - There are no statistically significant differences between the two majors (literary/scientific) in the academic compatibility of first year secondary school students in the valley. - There are no statistically significant differences between the two majors (literary/scientific) in the motivation to learn among first year secondary school students in the valley.
Academic compatibility and its relationship to motivation to learn among first year secondary students (A field study in the province of Debeila in Eloued - Algeria)
مقال
Keywords: التوافق؛ التوافق الدراسي؛ الدافعية؛ الدافعية للتعلم; compatibility, academic compatibility, motivation, Motivation to learn